Camptocormia as the presenting symptom in sporadic late onset nemaline myopathy: a case report - Matthias Türk; Armin M. Nagel; Frank Roemer; Ursula Schlötzer-Schrehardt; Christian T. Thiel; Martin Winterholler; Rolf Schröder (BMC Musculoskeletal Disorders, 2019)
Abstract Background Camptocormia has been reported in a plethora of diseases comprising disorders of the central nervous system, the peripheral nervous system, and the neuromuscular junction as well as hereditary and acquired myopathies. In sporadic late onset nemaline myopathy concomitant axial myopathy is common, but reports about camptocormia as the only presenting symptom in this condition are very rare. Notably, sporadic late onset nemaline myopathy is a potentially treatable condition in particular when associated with monoclonal gammopathy of unknown significance, HIV or rheumatological disorders. Case presentation We report the case of a 62-year-old female patient, who presented with slowly progressive camptocormia. Comprehensive work-up including neurological work-up, laboratory tests, MR-imaging, muscle biopsy and genetic testing led to the diagnosis of sporadic late onset nemaline myopathy. Conclusions Our case report highlights that sporadic late onset nemaline myopathy has to be considered in patients presenting with isolated camptocormia and comprehensive work-up of camptocormia is mandatory to ascertain the individual diagnosis, especially in consideration of treatable conditions.